Arbuscular Mycorrhizal Fungi Enhance Growth and Increase Concentrations of Anthocyanin, Phenolic Compounds, and Antioxidant Activity of Black Rice (Oryza sativa L.) - Sabaiporn Nacoon; Wasan Seemakram; Jindarat Ekprasert; Piyada Theerakulpisut; Jirawat Sanitchon; Thomas W. Kuyper; Sophon Boonlue (Soil Systems, 2023)
Black rice (Oryza sativa L.) contains high concentrations of bioactive compounds that are associated with human-health benefits. Arbuscular mycorrhizal fungi (AMF) can increase plant performance and concentrations of these bioactive compounds. In a pot experiment, the effects of four different species of AMF (Claroideoglomus etunicatum; Rhizophagus variabilis; Rhizophagus nov. spec.; Acaulospora longula) were assessed on growth performance, grain yield, concentrations of phenolic compounds and anthocyanin, and antioxidant activity of two black-rice cultivars. The experiment was a completely randomized factorial design with two factors, viz. cultivar (Niew Dam Hmong and Maled Phai) and treatment (four different species of AMF and two non-inoculated treatments, without and with mineral fertilizer). Results showed that cultivar, treatment, and their interaction were almost always significant sources of variation for both plant performance parameters and concentrations of bioactive compounds. Maled Phai showed higher performance and higher concentrations of phenolics and anthocyanins but lower antioxidant activity than Niew Dam Hmong. The non-inoculated treatment without mineral fertilizer showed the lowest performance. The non-inoculated treatment with mineral fertilizer resulted in larger root and shoot biomass than the mycorrhizal treatments, but grain yield was higher in the mycorrhizal treatments. Inoculation with R. variabilis resulted in the highest concentration of phenolics and anthocyanins. We conclude that R. variabilis was the best inoculum for increasing grain yield and bioactive compounds, especially in Maled Phai.